Innovative Approaches to the Management of Commercial and Economic Activities of Environmental Enterprise - “Spicy Pack” - ARANCHIY, Valentyna; YASNOLOB, Ilona; DEMIANENKO, Nataliia; BEZKROVNYI, Oleksandr; MYKHAILOVA, Olena; PYSARENKO, Svitlana; CHIP, Liudmyla; ARESTOV, Oleksandr; HORBATIUK, Liudmyla (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020, 2020)
The comparison of eco-friendliness of paper packaging materials from wood and alternative raw materials (straw, fallen leaves, etc.) with polyethylene packaging was made. The analysis was conducted according to the following criteria: consumption of raw materials, electricity, rubbish formation, and price of selling products. Advantages and drawbacks of each raw material type were characterized. It has been mentioned that polymers make a considerable and increasing part in manufacturing packaging materials. The prospects of producing paper bags from leaves and their sales prices were analyzed. The terms of degradation of packages made from different materials were analyzed. The conclusion has been made that paper from fallen leaves is not cheap, but it is important considering its environmental safety.  SWOT analysis of “Spicy pack” enterprise’s activity was analyzed (it will be engaged in manufacturing spicy packages for food products from innovative raw materials). The expediency of making spicy packages for food products was substantiated. In particular, ‘Spicy pack” logo consisting of only eco-paper (made from fallen leaves) and spices was suggested. Such packaging will help prolong 4 times food products’ suitability.  Such spices as cloves, rosemary, oregano, curcuma, and sage having antiseptic properties will be added to packages and napkins. These products will be reused for two-three weeks, then spices vanish, and the paper can be processed.